Prognostic implications of severe coronary calcification in patients undergoing coronary artery bypass surgery: An analysis of the SYNTAX Study. Issue 2 (27th May 2014) - Bourantas, Christos V.; Zhang, Yao‐Jun; Garg, Scot; Mack, Michael; Dawkins, Keith D.; Kappetein, Arie Pieter; Mohr, Friedrich W.; Colombo, Antonio; Holmes, David R.; Ståhle, Elisabeth; Feldman, Ted; Morice, Marie‐Claude; et al.
<x xml:space="preserve">Abstract</x> Objectives To investigate the prognostic implications of the presence of severe lesion calcification in patients undergoing coronary artery bypass graft (CABG) operation. Background There is robust evidence that lesion calcification is a predictor of worse prognosis in patients undergoing percutaneous coronary intervention; however, there is limited data about the prognostic implication of lesion calcium in patients treated with CABG. Methods We retrospectively analyzed data from 1, 545 patients who underwent CABG and were recruited in the SYNTAX study and CABG registry. Two experts reviewed the angiographic data and classified patients in two groups: those with severely calcified coronary arteries and those without severe lesion calcification. Clinical outcomes at 5‐year follow‐up were collected and compared in the two groups. Results One out of three patients exhibited severe lesion calcification (n = 588). Patients with calcified coronaries had an increased mortality at 5‐year follow‐up (17.1% vs. 9.9%, P < 0.001) and a higher event rate of death‐myocardial infarction (MI) compared with those without (19.4% vs. 13.2%, P = 0.003), but there was no statistical significant difference between the two groups for major adverse cardiovascular events (MACE, 26.8% vs. 21.8%, P = 0.057). In multivariate Cox regression analysis severe lesion calcification was an independent predictor of an increased all‐cause mortality (hazard ratio: 1.39, 95% confidence interval: 1.02–1.89; P = 0.037) but it was not an independent predictor of the combined end‐points death‐MI or MACE. Conclusions Severe lesion calcification is associated with an increased mortality in patients undergoing CABG, but it is not an independent predictor of death‐MI or MACE. This paradox can be attributed to the fact that CABG allows perfusion of the healthy coronaries bypassing the diseased arteries and thus it minimizes the risk of coronary events due to progressive atherosclerosis. © 2014 Wiley Periodicals, Inc.